ANRIL regulates retinoblastoma progression via targeting autophagy by miR-328-3p/TSC1/ULK signaling - Yang Yang; Yuezhi Zhang; Yanmei Fu; Shuanglian Li; Xiaolong Yin (Polish Journal of Pathology)
Retinoblastoma is the most common primary intraocular malignancy of childhood. The aim of our study was to investigate the role and regulatory mechanism of the long non-coding RNA ANRIL in retinoblastoma. Here, our data demonstrated that ANRIL overexpression inhibited miR-328-3p expression, but promoted expression of autophagy-related proteins (LC3B, ATG5, and BECN1). Then we predicted the binding sites for ANRIL with miR-328-3p, and for miR-328 3p with TSC1/ULK2 3′-UTR, and confirmed the combination of miR-328-3p and ANRIL and TSC1/ULK2 3′-UTR. Importantly, the data showed that ANRIL overexpression promoted TSC1 and ULK2 expression, and inhibited the phosphorylation of mTOR. Finally, our results indicated that ANRIL overexpression facilitated Y79 cell proliferation and cisplatin-induced apoptosis. Our results indicated that ANRIL promoted the proliferation and cisplatin resistance of Y79 cells through activating autophagy by promoting TSC1/ULK2 ex- pression via acting as a miR-328-3p sponge.